New media and democracy: the changing political landscape in Malaysia - Ali Salman; Mohd Safar Hasim (Universiti Kebangsaan Malaysia, 2011)

(untitled)
The new media, the Internet, has been used by businesses, government bodies, organisations, individuals etc. to conduct business, services and social transactions. The development and ascendancy of the Internet as an informational medium, has altered the information environment in which political elites and interested citizens function (Woodly 2008). In Malaysia, for example, the Internet is used as an alternative to mainstream media which is viewed as being pro-establishment. As of now there are a few online newspapers, such as Malaysiakini, The Malaysian Insider and blogs, with some of the blogs being run by former journalists. The run-up to Malaysia’s March 2008 General Elections had seen the Internet becoming a key political battleground for the first time as the use of ICT comes into full bloom with the opposition parties using the medium more than the Government parties. Some characteristics of Habermas concept of public sphere was truly mirrored in the run up to the General Elections and its aftermath where the Internet, via blogs, served as a public sphere for voters. As one of the characteristics of the public sphere where all citizens are guaranteed access, with the advent of the Internet, anyone with a computer and Internet connection (including wireless) can have access to the Internet. The new media has gradually penetrated the Malaysian political scenario affecting the status quo as seen in the March 2008 General Elections. The government can no longer under estimate the power and influence of the new media.